The Unconvinced Vote: The Nature and Determinants of Voting Intentions and the Changing Character of South African Electoral Politics. (2nd October 2019) - Roberts, Benjamin J.; Struwig, Jarè; Gordon, Steven L.; Davids, Yul Derek
ABSTRACT: In the lead up to South Africa's sixth National and Provincial Elections in May 2019, the recent performance and leadership dynamics within the country's major political parties raised fundamental concerns about the potential impact on voter turnout. These concerns were not unfounded, given that the 2019 General Elections recorded the lowest voter turnout since 1994, with only 49% of the voting age public participating. Despite this, relatively little remains known about the factors that differentiate decided voters from abstainers, undecided voters and undisclosed voters. To contribute further to the understanding of the determinants of planned electoral participation in the country, this article tests several dominant theoretical accounts of turnout using cumulative data from sixteen annual rounds of the South African Social Attitudes (SASAS) series conducted between 2003 and 2018. Specifically, the relative influence of key socio-demographic attributes, psychological engagement and regime evaluations is examined. The results point to psychological engagement variables playing a decisive role in separating different categories of voter, with age and education also exerting an influence. The article concludes by reflecting on the role of the unconvinced vote in the 2019 Elections, teasing out the implications for future elections in the country.